Experimental investigation of the performance of flutter-based microgenerators - Kafafy, Raed; Javeed, Abdulhakeem; Ihsan, Sany Izan; Idres, Moumen (2013)
Many wind harvesters have a high cut-in speed which is not available in many locations over long periods of time. The average wind speed round the year at most locations is 3-5 m/s. A novel and inexpensive low wind speed harvester design is proposed and tested in this work, winds and artificial airflows with speeds as low as 1 m/s can be harvested to generate usable electric voltage which is fed into a power conditioning and storage circuit. A commercially available micropower step up booster, conditioning and storage circuit is used and the harvester’s ability to integrate is demonstrated. Voltage and power outputs for various wind speeds are studied at different resistive loads